ESCHERICHIA COLI RESISTANCE CAUSES COLIBACILLOSIS TO ANTIBIOTICS IN PIG FARMS IN ALOK DISTRICT SIKKA REGENCY OF NTT - Pyo, Paulus Oktavianus; Mahatmi, Hapsari; Tenaya, I Wayan Masa (Buletin Veteriner Udayana, 2024)
The phenomenon of antibiotic resistance is a very serious problem that needs attention and countermeasures, especially in the use of antibiotics on farms, especially in pigs. This study aimed to determine the resistance of Escherichia coli that causes colibacillosis to several types of antibiotics. The study sample was taken based on purposive sampling from pigs showing symptoms of colibacillosis. A total of ten faecal samples were taken from a total population of 257 heads from 32 pig farms. Antibiotic resistance tests were performed using the Kirby-Bauer disc diffusion method. Results showed that all samples examined were E. coli with haemolysis γ and resistant to ampicillin, bacitracin, erythromycin (90%) and streptomycin (10%). But all isolates were sensitive to chloramphenicol, sulfamethoxazole, doxycycline and kanamycin (90%) and streptomycin (70%). The isolated E. coli showed cross-resistance to antibiotics ampicillin, bacitracin, erythromycin and streptomycin. It was concluded that E. coli was resistant to a number of antibiotics and some were even multidrug resistant. The use of antibiotics ampicillin, bacitracin, erythromycin and streptomycin in pig farms in Alok district, Sikka regency should be stopped considering that there has been resistance to isolated E. coli.